Sixth Five Year Plan Special Component Plan 1980-85 and 1981-82 Union Territory of Pondicherry - Planning Commission (Planning Commission, 1980)
It is proposal to work out a moment for each family including the various scheme that would cover the individual finally so that the income generated and social facilities provided would enable the family to cross the poverty line during the specified year.
Government of Pondicherry, Planning and Research Department